I would help but I'm not sure what you are asking for us to do
Answer:
a 3 + b 3 = (a + b) (a 2 − a b + b 2 ). Substituting a = x and b = 3 into the formula yields: x 3 + 27 = (x + 3) (x 2 − 3 x + 9).
Step-by-step explanation:
The rewritten form of the expression given in the task content in which case, the properties of the logarithm are used is; log2(z³/y²) + log9(y⁴x¹²).
<h3>What is the equivalent expression to the logarithmic expression given in the task content?</h3>
It follows from the task content that the logarithmic expression given in the task content is;
log2z + 2log2z + 4log9y + 12log9x - 2log2y
In which case, all terms are to their respective logarithmic bases.
Hence, it follows that; we have;
log2z³ - log2y² + log9y⁴ + log9x¹²
= log2(z³/y²) + log9(y⁴x¹²)
Read more on logarithm laws;
brainly.com/question/10208274
#SPJ1
Answer:
36
Step-by-step explanation:
u need 12 to make 4 bracelets
4 bracelets x 3 = 12 bracelets
12 beads x 3 = 36 beads